2019
DOI: 10.3390/molecules24152743
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Artificial Metalloproteins and Metalloenzymes with Metal Clusters

Abstract: Metalloproteins and metalloenzymes play important roles in biological systems by using the limited metal ions, complexes, and clusters that are associated with the protein matrix. The design of artificial metalloproteins and metalloenzymes not only reveals the structure and function relationship of natural proteins, but also enables the synthesis of artificial proteins and enzymes with improved properties and functions. Acknowledging the progress in rational design from single to multiple active sites, this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 133 publications
(181 reference statements)
0
19
0
Order By: Relevance
“…In addition to a single metal ion or metal cofactor, metalloproteins may harbor multiple metal ions forming metal clusters that play either structural roles, electron-transfer, or catalysis functions [47]. Metallothioneins (MTs) are metalloproteins with metal-clusters and play important roles in both detoxification of heavy metals and scavenge of reactive oxygen species (ROS) [48].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a single metal ion or metal cofactor, metalloproteins may harbor multiple metal ions forming metal clusters that play either structural roles, electron-transfer, or catalysis functions [47]. Metallothioneins (MTs) are metalloproteins with metal-clusters and play important roles in both detoxification of heavy metals and scavenge of reactive oxygen species (ROS) [48].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…Acharya and Blindauer reported that UO2 2+ can bind to the cyanobacterial metallothionein SmtA, and form a heterometallic (UO2 2+ )nZn4SmtA species, without alteration of the native Zn4Cys9His2 cluster [49]. 1 H-NMR and molecular modeling studies In addition to a single metal ion or metal cofactor, metalloproteins may harbor multiple metal ions forming metal clusters that play either structural roles, electron-transfer, or catalysis functions [47]. Metallothioneins (MTs) are metalloproteins with metal-clusters and play important roles in both detoxification of heavy metals and scavenge of reactive oxygen species (ROS) [48].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…[29] Currently, there is a tremendous interest in the redesign of metal coordination sites. [30,31,32] These centres or clusters can serve as reaction co-factors [33,34], to aid in the electron transfer [35,36], or to serve as scaffolds to carry quantum dots for bio-imaging, sensing or co-catalysis [37,38,39,40,41,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively less studied, Mo-clusters have shown promising electrocatalytic activities due to their intermediate behaviors between metal-coordination from comparing structures, properties, and reactivities of metalloenzymes and artificial catalysts [14]. Although relatively less studied, Mo-clusters have shown promising electrocatalytic activities due to their intermediate behaviors between metal-coordination complexes and nanoparticle catalysts [15]. In the perspective of developing efficient electrocatalysts, Mo-nanomaterials, which have shown remarkable electrocatalytic activities, should be considered together.…”
Section: Introductionmentioning
confidence: 99%